ANALISIS VISUAL GAME ARENA OF VALOR SEBAGAI DASAR PENGEMBANGAN KONSEP VISUAL GAME - Ricky Widyananda Putra; Benny Muhdaliha (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2017)
In game design, in addition to having a powerful and interesting gameplay concept, creator should pay attention to the visual aspect embodied in the visual design of the game. Visual aspect is so important to attract user to play it, especially in Multiplayer Online Battle Arena (MOBA) genre game. With the support of visual design, users can easily understand and follow the gameplay faster and and surely they can understand the ability of each character with ease. This research tries to study the visual design and characters design of Arena Of Valor game. With visual perception theory and manga matrix theory to gain an understanding of the visual approach and creator considerations in the game visual design. Hopefully this research can be used as the basis reference for further MOBA game development.